Woleaian-English Dictionary - Sohn, Ho-min (PALI Language Texts-Micronesia, 1976)
This was the first dictionary compiled for the language spoken on Woleai Atoll in the Caroline Islands. The dictionary contains some 6,200 Woleaian entries and an English-Woleaian finder list of about 4,000 entries. The Woleaian entries are based on an alphabetic system of orthography developed by the authors. Each entry also contains, where appropriate, the following parts: loan source, alternant forms, part of speech or word-class, grammatical notes, definitions, phrase examples, sentence examples, synonyms, antonyms, and cross-references.